Utility of immunohistochemistry method in expression of thyroid transcription factor-1 in endometrial and endocervical adenocarcinoma - Janbazvatan A (Tehran University Medical Journal, 2011)
"nBackground: Thyroid transcription factor-1 (TTF-1) is widely used in the diagnosis of lung and thyroid carcinomas. Although there have been reports of TTF-1 immunoreactivity in tumors other than those originating from the lung or thyroid, endocervical and endometrial adenocarcinomas have not been studied in large numbers in this regard."n "nMethods: Thirteen endocervical adenocarcinomas, 39 endometrioid endometrial adenocarcinomas and four uterine serous carcinomas which had no neuroendocrine component were retrieved, stained by TTF-1 and examined. A semiquantitative grading system was used to evaluate the distribution of TTF-1 staining (0= negative, 1+  5%, 2+= 5% to 25%, 3+= 26% to 50%, 4+= 51% to 75% and 5+  75%). A qualitative system was also used to evaluate the intensity of TTF-1 staining (weak, moderate and strong)."n "nResults: TTF-1 expression was seen in 1 out of 13 (7.7%) endocervical adenocarcinoma samples, showing 1+ distribution rate and weak intensity. The positive sample was moderately differentiated. TTF-1 expression was present in 2 out of 39 (5.1%) endometrioid adenocarcinoma samples (one grade I and the other grade II) with 1+ distribution rate and weak intensity. There was no apparent correlation between the degree of differentiation and TTF-1 positivity in the studied adenocarcinomas. None of the four endometrial serous carcinomas were positive for TTF-1."n "nConclusion: Although some recent studies cast doubt about the specificity of TTF-1 for lung and thyroid carcinoma, our study showed that TTF-1 was negative in endocervical and endometrial adenocarcinomas and established the specificity of TTF-1 for lung and thyroid carcinomas.